PAEDIATRIC GRAVES’ DISEASE AND DEFINITIVE TREATMENT - Hui, Saw Shi; Zaini, Azriyanti Binti Anuar; Samingan, Nurshadia; Annie, Leong; Jalaludin, Muhammad Yazid Bin (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION Paediatric Graves’ disease (GD) is managed by antithyroid drugs (ATD), radioactive iodine (RAI) or thyroid surgery. This study aimed to describe the characteristics and outcomes of paediatric patients who received definitive therapy. METHODOLOGY Children and adolescents diagnosed with GD from 2012 to 2024 at the University Malaya Medical Centre were included in this retrospective review. RESULT A total of 37 patients were referred and diagnosed with GD; majority (78.4%) were female. Definitive therapy was given to 48%: 5 (35%) had total thyroidectomy and 9 (64%) received RAI. They had an average of four relapses during the disease. On average, the patients received ATD for 4.37 ± 2.28 years prior to the definitive treatment. The main factor in determining the choice of treatment was the size of the goitre. The mean goitre size for the RAI group was 21.68 ± 7.9 g, compared to 76.7 ± 22.88 g for the thyroidectomy group. Mean age in the RAI group was 15.53 ± 1.23 years. The youngest patient was 8 years old. Mean RAI dose was 9.3 ± 0.66 mCi. Six patients achieved hypothyroidism within 2.17 ± 2.44 months, while 1 patient achieved hypothyroidism 8 months post-RAI. Three had relapses post-RAI. Two patients required a second RAI one year later and achieved hypothyroidism within 2 to 4 weeks. Those who required a second RAI were given lower RAI doses initially (mean 5.6 ± 2.2 mCi). The mean age of patients who underwent total thyroidectomy was 17.08 ± 0.78 years. Two out of 5 patients developed hypocalcaemia postoperatively. None had vocal cord paralysis. CONCLUSION From this cohort, the onset of hypothyroidism post-RAI was varied. Lower doses of initial RAI were seen in patients who had relapsed and required a second treatment. Total thyroidectomy in children and adolescents is safe with minimal complications under the care of a high-volume surgeon.